Surface-Modified Nanocomposite Membranes. Issue 4 (2nd October 2018) - Lakhotia, Sonia R.; Mukhopadhyay, Mausumi; Kumari, Premlata
Abstract : Access to enough clean and safe water requires improvement over the current state of filtration technology. Membrane technology is one of the best tools for removing dissolved matters and/or particulates during the cleaning process, but some unavoidable intrinsic properties, like flux decline and fouling, reduce the membrane life, stability and separation capacity. To improve membrane performances, researchers reported the significant role played by associating nanoparticles to membrane polymers. Nanoparticles create a path in the membrane for selective water permeation and pose a barrier for undesired matters. There are two different methods for incorporating nanoparticles in membranes: (i) adding nanoparticles to the polymeric matrix and (ii) depositing nanoparticles on the membrane surface. The deposition/coating of nanoparticles on the membrane surface allows opportunities for water/wastewater treatment. In this review, focus has been given to the development of different nanoparticle-deposited membranes and their possible applications to large-scale water purification processes, where antifouling, permeate quality and self-cleaning properties are required.